2001
DOI: 10.1200/jco.2001.19.13.3163
|View full text |Cite
|
Sign up to set email alerts
|

Late Mortality Experience in Five-Year Survivors of Childhood and Adolescent Cancer: The Childhood Cancer Survivor Study

Abstract: While recurrent disease remains a major contributor to late mortality in 5-year survivors of childhood cancer, significant excesses in mortality risk associated with treatment-related complications exist up to 25 years after the initial cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
452
6
21

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 739 publications
(498 citation statements)
references
References 32 publications
19
452
6
21
Order By: Relevance
“…Analyses of 5-year conditional survival indicate that long-term survivors have an excellent chance of a cure but, as recent research suggests, survivors will require ongoing medical surveillance for many years after their diagnosis, given that the majority of late deaths among long-term survivors is due to the original RMS or the diagnosis of a second malignant neoplasm. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Analyses of 5-year conditional survival indicate that long-term survivors have an excellent chance of a cure but, as recent research suggests, survivors will require ongoing medical surveillance for many years after their diagnosis, given that the majority of late deaths among long-term survivors is due to the original RMS or the diagnosis of a second malignant neoplasm. 35 …”
Section: Discussionmentioning
confidence: 99%
“…With long-term survival rates in excess of 70%, it is anticipated that, by the year 2010, approximately 1 in 640 to 715 members of the adult population will be a long-term survivor of childhood cancer. [1][2][3] Impaired fertility in both males and females and adverse pregnancy outcomes are major concerns for the increasing population of survivors of childhood and young adult cancer. The challenge facing professionals is how to provide curative treatment while balancing the potential loss or impairment of fertility.…”
mentioning
confidence: 99%
“…A study of 5-year survivors of childhood cancer found an overall standardized mortality ratio that was 10.8 times greater than that of the general U.S. population. 2 Recurrence of the original malignancy is a major contributor, although mortality risk is also increased because of subsequent malignancies, cardiomyopathy and ischemic heart disease, and pulmonary fibrosis. 2 Long-term survivors also may suffer morbidity because of late effects of their cancer therapy.…”
mentioning
confidence: 99%
“…2 Recurrence of the original malignancy is a major contributor, although mortality risk is also increased because of subsequent malignancies, cardiomyopathy and ischemic heart disease, and pulmonary fibrosis. 2 Long-term survivors also may suffer morbidity because of late effects of their cancer therapy. Several small studies have demonstrated that approximately 2 in 3 long-term survivors will be affected by at least 1 late effect of therapy, with approximately 30% developing moderate to severe effects.…”
mentioning
confidence: 99%